PROFIL KONDISI FISIK ATLET PUTRI UKM BOLA BASKET UNIVERSITAS NEGERI SEMARANG TAHUN 2023 - Syahlan Yuanriza; Priyanto Priyanto (Unnes Journal of Sport Sciences, 2023)
This research was motivated by the decline in the physical condition of female basketball UKM athletes at Semarang State University in 2023 after the pandemic, resulting in a decrease in achievement. This research is a quantitative descriptive study, using a purposive sampling technique in sampling. The subjects of this study were 9 women's basketball UKM athletes at Semarang State University in 2023. The instruments used were the 1 minutes push up test, the sit and reach test, the two hands medicine ball put test, the 30 m running test, the Illinois agility test, and the Mutlifistage Fitness test. The results of this study indicate that the profile of the physical condition of female basketball UKM athletes at Semarang State University in 2023 is lacking with details on the athlete category, namely from 100% of athletes at 16.667% the average athlete has very good physical condition, 33.334% the average athlete has a physical condition moderate, and the average 50% of athletes have a poor physical condition. The conclusion of the research results states that the physical condition of the athletes of the Semarang State University women's basketball UKM in 2023 is in the poor category. The test results for measuring strength, power, speed, agility, and endurance are included in the category of medium and less.